Analisis Keanekaragaman Jenis Pakan Gajah Sumatra (Elephas maximus sumatranus) Jinak, Di ERU (Elephant Respon Unit) Tegal Yoso - Jilan Rona Mahfudziah; Gunardi Djoko Winarno; Bainah Sari Dewi; Sugeng P. Harianto (Universitas Lambung Mangkurat, 2024)
Sumatran elephant (Elephas maximus sumatrensis) is one of the protected animals in Indonesia according to Law Number 266 of 1931 and Decree of the Minister of Forestry Number 301/Kpts/II/1991. This species is included in the vulnerable list of the International Union for Conservation of Nature (IUCN) red list book with endangered status and is included in appendix I of the Convention on International Trades on Endangered Species of Wild Flora and Fauna (CITES) with prohibited status. trade. The aim of this research is to analyze the diversity of types of natural food for elephants at ERU Tegal Yoso, analyze the diversity of types of feed that fall at ERU Tegal Yoso, analyze the composition of artificial feed for elephants at ERU Tegal Yoso, analyze processing techniques for artificial feed for elephants at ERU Tegal Yoso. Food is the most important habitat component, food availability is closely related to seasonal changes, in the rainy season food is abundant while in the dry season food is reduced. The quality of feed will affect elephant consumption. This research was conducted in Tegal Yoso Village and ERU Tegal Yoso using survey, interview and vegetation analysis methods. The dominant tree in the tree and pole phase is the laban tree. In the sapling and seedling stages, the dominant tree is the rice tree. Making artificial feed by mixing ingredients such as green beans, corn, rice, minerals, salt, brown sugar, bran and water. This research obtained results of 22 types of tree species diversity in ERU Tegal Yoso and 13 types of trees eaten by elephants.Gajah sumatera (Elephas maximus sumatrensis) merupakan salah satu satwa yang dilindungi di Indonesia menurut Undang-Undang Nomor 266 Tahun 1931 dan Keputusan Menteri Kehutanan Nomor 301/Kpts/II/1991. Spesies ini masuk dalam daftar rentan International Union for Conservation of Nature (IUCN) red list book dengan status endangered dan masuk dalam appendix I Convention on International Trades on Endangered Species of Wild Flora and Fauna (CITES) dengan status terlarang. berdagang. Penelitian ini bertujuan untuk Tujuan dari penelitian ini yaitu Menganalisis keanekeragaman jenis pakan alami Gajah di ERU Tegal Yoso, menganalisis keanekaragaman jenis pakan drop in Gajah di ERU Tegal Yoso, menganalisis komposisi pakan buatan Gajah di ERU Tegal Yoso, menganalisis teknik pengolahan pakan buatan Gajah di ERU Tegal Yoso. Pakan merupakan komponen habitat yang paling penting, ketersediaan pakan sangat erat kaitannya dengan perubahan musim, pada musim hujan pakan melimpah sedangkan pada musim kemarau pakan berkurang. Kualitas pakan akan mempengaruhi konsumsi gajah. Penelitian ini dilakukan di Desa Tegal Yoso dan ERU Tegal Yoso dengan menggunakan metode survei, wawancara dan analisis vegetasi. Pohon yang dominan pada fase pohon dan tiang adalah pohon laban. Pada fase pancang dan semai, pohon yang dominan adalah pohon berasan. Pembuatan pakan buatan dengan mencampurkan bahan-bahan seperti kacang hijau, jagung, beras, mineral, garam, gula merah, dedak dan air. Penelitian ini memperoleh hasil keanekaragaman jenis pohon di ERU Tegal Yoso sebanyak 22 jenis dan jenis pohon dimakan gajah sebanyak 13 jenis